1988
DOI: 10.1677/joe.0.1190075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aldrin on spermatogenesis, plasma gonadotrophins and testosterone, and testicular testosterone in the rat

Abstract: Quantitative evaluation of the different varieties of germ cells at stage VII of the seminiferous epithelium cycle, namely type-A spermatogonia (ASg), preleptotene spermatocytes (pLSc), mid-pachytene spermatocytes (mPSc) and step 7 spermatids (7Sd), along with radioimmunoassay of plasma gonadotrophins (FSH and LH), testosterone and testicular testosterone were performed in Wistar rats following treatment with aldrin (polycyclic chlorinated hydrocarbon insecticide) for approximately one (13 days) or two cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…24,54 The exact mechanism through which quinalphos induces these alterations in testes is not clear. It has been reported that luteinizing hormone and folliclestimulating hormone, which are required to obtain nor-mal testicular function, are down-regulated in quinalphos-treated rats, 15,16,17,36 acting primarily at the level of the pituitary. 17 It has also been observed that an increase in testicular lipid peroxidation causes a decrease in the production of testicular androgen.…”
Section: Quinalphos-induced Destabilization Of Membrane Fluidity and mentioning
confidence: 99%
See 3 more Smart Citations
“…24,54 The exact mechanism through which quinalphos induces these alterations in testes is not clear. It has been reported that luteinizing hormone and folliclestimulating hormone, which are required to obtain nor-mal testicular function, are down-regulated in quinalphos-treated rats, 15,16,17,36 acting primarily at the level of the pituitary. 17 It has also been observed that an increase in testicular lipid peroxidation causes a decrease in the production of testicular androgen.…”
Section: Quinalphos-induced Destabilization Of Membrane Fluidity and mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Some of these pesticides have the ability to mimic the natural oestrogens, which are popularly known as xeno-oestrogens or environmental oestrogens, 10,11 and may have a damaging effect on the reproductive system and deleterious effects on the central nervous system function of both humans and wildlife. 4,10,[12][13][14][15][16] Earlier investigations revealed that different pesticides and insecticides, on their exposure to the reproductive system, cause varying degrees of testicular dysfunction and brain disorder in man and also in experimental animals. 13,15,16 Quinalphos (O,O-diethyl-O-[quinoxalinyl- (2)-thionophosphate]), one such environmental xeno-oestrogenic insecticide, is known to interfere with the expression of the sex hormones leading to abnormalities in both male and female reproductive organs in Wistar albino rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aldrin accumulates in the testis, although, to a lesser extent than in other tissues (66). Treatment of rats with aldrin inhibited intratesticular and circulating testosterone levels and affected spermatogenesis (67). Heptachlor is an insecticide used in the control of termites and in the cotton industry.…”
Section: Organochlorinesmentioning
confidence: 99%